Fenomena Prokrastinasi Akademik Pada Mahasiswa: Bagaimana Kaitannya Dengan Kecanduan Smartphone Saat Pandemi COVID-19 Berlangsung? - Novalyne, Patricia Oriza; Soetjiningsih, Christiana Hari (Psikoborneo: Jurnal Ilmiah Psikologi, 2022)
The purpose of this study is to determine the relationship between smartphone addiction and academic procrastination behavior during the Covid-19 pandemic. Participants totaled 203 active UKSW students obtained using purposive sampling techniques. The measuring instruments used in this study were the Indonesian version of smartphone addiction scale-short version (SAS-SV) with a total of 21 items with reliability r = 0.818 and an academic procrastination scale totaling 25 items with reliability r = 0.870. The results of the hypothesis test have a significant positive relationship between smartphone addiction and the academic procrastination of students during the Covid-19 pandemic. The results of the hypothesis test with the Spearman Rank correlation technique have a significant positive relationship between smartphone addiction and student academic procrastination during the COVID-19 pandemic. Smartphone addiction contributes 10.6% effectively to academic procrastination behavior while 89.4% is influenced by other factors such as physical or health conditions and psychological conditions, parental parenting and the environment such as the family environment, society, and schools. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara smartphone addiction dengan academic  procrastination  di masa pandemi covid-19.  Partisipan berjumlah 203 mahasiswa aktif UKSW yang diperoleh dengan menggunakan teknik accidental.  Alat ukur yang digunakan dalam penelitian ini adalah smartphone addiction scale-short version (SAS-SV) versi bahasa indonesia dengan jumlah 21 aitem dengan reliabilitas r=0,818 dan skala prokrastinasi akademik yang berjumlah 25 aitem dengan reliabilitas r=0,870. Hasil uji hipotesis dengan teknik korelasi Rank Spearman terdapat hubungan positif signifikan antara smartphone addiction dengan academic procrastination mahasiswa di masa pandemi covid-19. Smartphone addiction memberikan sumbangan efektif sebesar 10,6% pada academic procrastination sedangkan 89,4% dipengaruhi oleh faktor-faktor lainnya seperti kondisi fisik atau kesehatan dan kondisi psikologis, pola asuh orangtua dan lingkungan seperti lingkungan keluarga, masyarakat, dan sekolah.